petrescutz
4

# Sa se rezolve ecuatiile: a)5(x-7)-2x=x-41 b)7(x-9)-4x=x-39 c)4(x+5)-3(x-3)=2(x+15) d)5(x+2)-4(x-2)=3(x+8) e)2(15+3(x-1))=4(x+7) f)2(4(x-2)+16)=6(x+5) g)3(4x-3(x+5))+19=2(x-23) h)3(5x-4(x+3))+21=2(x-17) Va rooog d-au si coroana va rooog e urgent!!!

(1) Răspunsuri
TheTytek

a) 5(x-7)-2x = x-41 5x-35-2x = x-41 3x-35 = x-41 3x-x = -41+35 2x = -6 x = -6/2 x = -3. b) 7(x-9)-4x = x-39 7x-63-4x = x-39 3x-63 = x-39 3x-x = -39+63 2x = 24 x = 24/2 x = 12. c) 4(x+5)-3(x-3) = 2(x+15) 4x+20-3x+9 = 2x+30 x+29 = 2x+30 x-2x = 30-29 -x = 1 x = -1. d) 5(x+2)-4(x-2) = 3(x+8) 5x+10-4x-8 = 3x+24 x+2 = 3x+24 x-3x = 24-2 -2x = 22 x = -11. e) 2[15+3(x-1)] = 4(x+7) 2(15+3x-3) = 4x+28 2(12+3x) = 4x+28 24+6x = 4x+28 6x-4x = 28-24 2x = 4 x = 2. f) 2[4(x-2)+16] = 6(x+5) 2(4x-8+16) = 6x+30 2(4x+8) = 6x+30 8x+16 = 6x+30 8x-6x = 30-16 2x = 14 x = 7. g) 3[4x-3(x+5)]+19 = 2(x-23) 3(4x-3x-15+19) = 2x-46 3(x+4) = 2x-46 3x+12 = 2x-46 3x-2x = -46-12 x = -58. h) 3[5x-4(x+3)]+21 = 2(x-17) 3(5x-4x-12)+21 = 2x-34 3(x-12)+21 = 2x-34 3x-36+21 = 2x-34 3x-15 = 2x-34 3x-2x = -34+15 x = -19. I hope I helped you :)